C0045 Ultrasound-guided ultraminimally invasive plantar fascia release. (5th July 2018) - Iborra, Alvaro; Villanueva, Manuel; Benito, Felipe; Sanz, Pablo; Fabian, Guillermo Rodriguez
Abstract : Background: Ten percent of the population present with heel pain during their lifetime. More than 80% of these patients are active working adults between the ages of 25 and 65 years. Plantar fasciitis is the most common cause of heel pain in patients presenting at the outpatient clinic. Today, plantar fasciitis is considered a degenerative disorder of the fascia caused by overuse stress rather than an inflammatory process. Consequently, a more appropriate term would be plantar fasciosis. Ultrasound is an inexpensive diagnostic tool that enables comparison with the contralateral side and can be used for continuous monitoring of injuries. It is also helpful for minimally invasive treatm. Methods: We performed US-guided plantar fascia release in 24 patients (26 cases) with chronic plantar fasciosis. Patients had received multiple previous conservative treatments for 1–3 years. However, their symptoms failed to resolve. Preoperative plantar fascia thickness ranged 0.7–1.2 cm. The instrument set included long needles (a 16-gauge, 1.7 mm diameter Abbocath, a V-shaped straight curette, a blunt dissector, a hook knife and an ultrasound device (Alpinion ECube15) with a 10–17–MHz linear transducer. Surgical technique: u sing ultrasound, we first identify the insertion of the plantar fascia in the calcaneal tuberosity in a longitudinal plane. We make a 1–2 mm incision at the selected medial entry point. We measure the mediolateral width of the plantar fascia and then insert the blunt dissector between the fascia and the muscle to half the width of the fascia. The hook blade is then inserted. The curved scalpel is placed dorsal or deep to the plantar fascia and superficial to the muscle. We turn the hook knife towards the plantar fat pad rather than the calcaneus and release the fascia from lateral to medial. Results: The study population comprised 15 males and 9 females. There were two bilateral cases. Mean age was 39 years (37–59). Preoperative VAS averaged 9 (8–10), AOSFAS averaged 30 points. Postoperative VAS averaged 1 (0–2) and AOSFAS 91 points (74–100). Conclusions: Ultrasound-guided release allows us to control damage to the plantar muscles and visualise the width and depth of the fascia. The procedure we describe is safe, precise Surgical damage is minimal, It can be performed with regional anaesthesia, under an outpatient regimen. It does not require ischemia, stitches or special, thus reducing wound healing problems and contraindications in patients with diabetes or vascular insufficiency.